On the sustainability of rubberized concrete filled square steel tubular columns. (1st January 2018) - Duarte, A.P.C.; Silvestre, N.; de Brito, J.; Júlio, E.; Silvestre, J.D.
Abstract: This work presents a comparative assessment of the sustainability, from a life cycle perspective, of a concrete filled square steel tubular (CFSST) column, using rubberized concrete (RuC), thus designated 'RuCFSST'. RuCFSST columns are structural members that take advantage of the optimized structural performance of CFSST columns and of the improved ductility of RuC compared to that of natural aggregate concrete (NAC). Besides the two most obvious environmental advantages of using RuC instead of NAC in CFSST columns - reductions of tyre disposal into landfills and of extraction of natural aggregates - it is shown that a more complete assessment of the sustainability of RuC and RuCFSST columns is required. Hence, the embodied energy (EE), thermal performance, cost, expected durability and recycling potential of the RuCFSST column analyzed are assessed and compared with those of a CFSST column and a reinforced concrete (RC) column, all three having similar mechanical performance. It is shown that the analyzed RuCFSST column has a marginal higher EE and cost than those of the CFSST column - differences less than 1%. Conversely, the thermal transmittance coefficient of the former is lower than that of the latter, which improves its behaviour concerning thermal bridges. Compared to the composite solutions, the RC column possess circa 35% more EE but is about 25% less expensive. Overall, the RuCFSST and CFSST columns incorporate a similar total energy (includes the contribution of the EE and thermal performance during service life), which is 25% lower than that of the RC column. Graphical abstract: Image 1 Highlights: Sustainability analysis of rubberized concrete filled square steel tubular (RuCFSST) column. Comparison with concrete filled square steel tubular (CFSST) and reinforced concrete (RC) columns. RuCFSST and CFSST columns incorporate less 30% embodied energy (EE) than RC column. Rubberized concrete increases (< 1%) EE but decreases (< 1%) heat gains (HG) and losses (HL) of RuCFSST compared to CFSST. Total energy (TE = EE + HG + HL) in 50 years life span of RuCFSST column is 25% lower than that of RC column.